Electrodeposition of poly(3,4-ethylenedioxythiophene)/reduced graphene oxide/manganese dioxide for simultaneous detection of uric acid, dopamine and ascorbic acid - Tukimin, Nurulkhalilah; Abdullah, Jaafar; Sulaiman, Yusran (Elsevier, 2018)
A simple and sensitive sensor of poly(3,4-ethylenedioxythiophene)/reduced graphene oxide/manganese dioxide modified glassy carbon electrode (PrGO/MnO2) was fabricated via cyclic voltammetry (CV) for simultaneous detection of uric acid (UA), dopamine (DA) and ascorbic acid (AA). The PrGO/MnO2 composite film possessed excellent electrocatalytic rate and high selectivity towards the oxidation of UA, DA and AA in 0.1 M PBS (pH 6.0). The peak potential separation (∆Ep) of AA-DA, AA-UA and DA-UA were 166, 312 and 146 mV, respectively. The detection limits of 1.00, 0.02 and 0.05 μM with a linear response of 1–800, 0.03–45 and 0.3–80 μM were obtained for AA, DA and UA, respectively. This sensor also showed an excellent stability (reproducibility and repeatability).